1987
DOI: 10.1056/nejm198706043162303
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intervals between Doses on the Development of Tolerance to Isosorbide Dinitrate

Abstract: We studied the development of tolerance to isosorbide dinitrate in 12 patients with chronic stable angina pectoris. The effect of 30 mg of isosorbide dinitrate on treadmill exercise performance was assessed before and at one, three, and five hours after a single dose. As compared with placebo, the drug increased treadmill walking time until the onset of angina and until the development of moderate angina over the five-hour observation period (P less than 0.05). The patients then received 30 mg of isosorbide di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
3

Year Published

1988
1988
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(47 citation statements)
references
References 16 publications
2
42
0
3
Order By: Relevance
“…Its development is most frequently associated with those formulations or dosage regimes which attempt to provide a constant plasma nitrate level (Thadani et al, 1982;Parker & Fung 1984;Parker et al, 1987a, b). In this respect, transdermal nitroglycerine patches, which deliver GTN across the skin at a constant rate over a 24 h period, have been particularly implicated (James et al, 1985;Jordan et al, 1985;Thadani et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Its development is most frequently associated with those formulations or dosage regimes which attempt to provide a constant plasma nitrate level (Thadani et al, 1982;Parker & Fung 1984;Parker et al, 1987a, b). In this respect, transdermal nitroglycerine patches, which deliver GTN across the skin at a constant rate over a 24 h period, have been particularly implicated (James et al, 1985;Jordan et al, 1985;Thadani et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…In most mammals nitric oxide is involved in the regulation of many pathways including the cardiovascular, respiratory and nervous systems 64 . Nitric oxide has also been proven to show beneficial effects against some diseases and as such have found roles as antianginal drugs and some anti-inflammatories 65 .…”
Section: Figure 30mentioning
confidence: 99%
“…2,5,6,21,22 A recent FDA advisory meeting concluded that interruption of nitrate exposure for as little as 8-12 h is the best means of preventing or reversing tolerance. 4 However, to our knowledge, there have been no previous investigations of the intracellular production of cGMP, the vasodilatory response and activation of neurohormonal factors during intermittent NTG therapy.…”
Section: Intermittent Nitroglycerin Therapy and The Rebound Phenomenonmentioning
confidence: 99%